The Resilience of Families who Live in a Disaster-Prone Location in terms of Disaster Preparedness: A Scoping Review - Sriyono, Sriyono; Nursalam, Nursalam; Hamzah, Hamzah (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Post-disaster difficulties and problems are closely related to the level of family resilience. 50% of Lapindo mudflow victims in Indonesia have faced delays in getting disaster compensation due to having low resilience. Meanwhile 60% - 70% of riverbank residents in the UK have never been prepared due to low resilience. Objective: To explore the research that has been done related to the topic of family resilience living in disaster-prone locations in terms of disaster preparedness. Method: The study design was a scoping review where data were searched through the Medline and Scopus databases. Data analysis was performed using qualitative thematic analysis. Result: 20 articles were found that met the inclusion criteria. Themes that emerged from the basic research analysis included: definition of preparedness according to family, factors affecting disaster perceived risk, inter-family factors and intra-family factors that increase resilience. Discussion: Emotional and religious support can help shape coping and positive thinking so as to increase family resilience. An intervention that includes religion and increased resilience can fill a few gaps in understanding the science of resilience in preparing for disasters.